Implementation of Entrustable Professional Activities assessments in a Canadian obstetrics and gynecology residency program: A mixed methods study - Mueller, Valerie; Morais, Michelle; Lee, Mark; Sherbino, Jonathan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2022)
Background: Since the implementation of competency-based medical education (CBME) across residency training programs in Canada, there has been limited research understanding how entrustable professional activity (EPA) assessments are used by faculty supervisors and residents.Objective: This study examines how EPA assessments are used in an Obstetrics and Gynecology residency program and the impact of implementation on both groups.Methods: A mixed methods study design was used. Part one involved the aggregation of descriptive data of EPA assessment completion for postgraduate year 1 and 2 residents from July 2019 to May 2020. Part two involved a thematic analysis of semi-structured interviews of residents and faculty.Results:  There was significant uptake of EPA assessments across community and teaching hospitals with widespread contribution of assessment data from faculty. However, both residents and faculty reported that the intended design of EPA assessments as low-stakes assessments to provide formative feedback is not how EPA assessments are experienced. Residents and faculty noted the increased level of administrative burden and related perceived stress amongst the resident group.  Conclusions: The implementation of EPA assessments is feasible across a variety of sites. However, previous measurement challenges remain. Neither residents nor faculty perceive the value of EPAs to improve feedback, despite their intended nature.